PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION APOTEKER PADA RS X DI KOTA BANDUNG - Dwi Puspita Sari; Bunga Destyana Anggun Paramita (Jurnal Inovasi Penelitian, 2022)
Human resources are one that is very important and cannot be separated from an organization, in essence human resources are movers, thinkers and planners to achieve the goals of the organization. Good management and management of human resources will result in a company that will continue to achieve good progress and development. There are many factors that influence the development of human resources in an organization or company, and these factors differ in each company. This study aims to describe, test and analyze whether the effect of job satisfaction can affect the performance of a pharmacist in a pharmacy installation at hospital X in Bandung totaling 25 people. The method used is multiple linear regression with the help of SPSs version 24.0. The results of the study show that there is a significant influence between the effect of job satisfaction on employee performance.